On-line removal of sulfide interference in phosphate determination by flow injection analysis - Michael Grace (2018)
Simple on-line sulfide removal using potassium permanganate (KMnO 4) was incorporated into a spectrophotometric flow injection (FI) system for phosphate determination using molybdenum blue with ascorbic acid as the reductant. Excess KMnO 4 was reduced before the sample zone passed through the detector and the method effectively removed all sulfide interference. Without this removal, sulfide interference caused major errors in filterable reactive phosphorus (FRP) analyses. Some model organic phosphates were tested with the permanganate manifold and there was no conversion to phosphate. With the KMnO 4 carrier, the calibration plot was linear over the tested range (0-1000 μg L -1 P), with a detection limit of 38 μg L -1 P. Precision was typically better than 2.5%, based on triplicate injections. FRP determinations on anoxic, estuarine pore water samples were in excellent agreement with the conventional batch method with prior acidification and sparging, but avoided sample pretreatment and the generation of toxic H 2S. Samples spiked with phosphate gave recoveries of 93-104%. Given the simplicity of modifying conventional FI manifolds to incorporate the improvements described here, it is recommended that all FRP measurements by FI replace water as the carrier with 0.01 M KMnO 4 whenever the presence of sulfide is suspected. © CISRO 2006.